2011
DOI: 10.1002/jrs.3029
|View full text |Cite
|
Sign up to set email alerts
|

SERS study of methylated and nonmethylated ribonucleosides and the effect of aggregating agents

Abstract: We present surface-enhanced Raman scattering (SERS) spectra of the RNA nucleosides adenosine, cytidine, guanosine and uracil and the methylated derivatives 5-methylcytidine and 7-methylguanosine, a class of important nucleic acid components that has not previously been well characterised using SERS spectroscopy. Our work shows that the selection of aggregating agent plays a crucial role for SERS analysis of these nucleosides with K 2 SO 4 generating immediate enhancement while NaCl only gave immediate enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…The spectral peaks in Fig. 6c are also somewhat similar to the spectra of adenosine and guanosine 24,32 , albeit with a peak shift towards the red of 20 cm À 1 .…”
Section: Nature Communications | Doi: 101038/ncomms6144mentioning
confidence: 53%
See 1 more Smart Citation
“…The spectral peaks in Fig. 6c are also somewhat similar to the spectra of adenosine and guanosine 24,32 , albeit with a peak shift towards the red of 20 cm À 1 .…”
Section: Nature Communications | Doi: 101038/ncomms6144mentioning
confidence: 53%
“…This emphasizes the importance of spatial resolution and targeted nanoparticle fabrication. In typical SERS measurements of a purified analyte, aggregation of nanoparticles is often intentionally induced since it changes the amount of detectable signal 24 . In the photoreduction process, the detection of SERS from fabricated regions likely occurs due to the growth of small particles, trapping biological molecules between particles, at hotspots in the enhanced field, creating ideal conditions for measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Hobro, Abdali, and Blanch reported a SERS study of methylated and nonmethylated ribonucleosides and the effect of aggregating agents. Their work shows that the selection of aggregating agent plays a crucial role for SERS analysis of these nucleosides with K 2 SO 4 generating immediate enhancement, whereas NaCl gives immediate enhancement only for the pyrimidine nucleosides . Jurasekova et al .…”
Section: Sersmentioning
confidence: 99%
“…However, label-free methods do have the distinct advantage that they are intrinsically sensitive to chemical modifications of DNA, since chemical modification of nucleobases causes characteristic changes in their Raman spectra. [6][7][8][9][10][11][12][13][14] For example, it has been shown that substitution of even a single base in 25-mer oligodeoxynucleotides (ODNs) can be detected using SERS difference spectroscopy. 6 This sensitivity to changes in chemical structure means that SERS may be also used to detect post-transcription modifications of nucleobases, which are both important from a physiological/clinical viewpoint and difficult to detect through hybridisation assays.…”
Section: Introductionmentioning
confidence: 99%